PENETAPAN KADAR SARI LARUT AIR DAN SARI LARUT ETANOL SIMPLISIA DAUN KERSEN (Muntingia calabura L.) - Nadania Issnann Romadhani; Fara Azzahra; Octariana Sofyan (Journal Pharma Saintika, 2025)
Abstract: The kersen leaves contain of chemical compounds such as a flavonoids, alkaloids, tannins and saponin. Standardization of kersen leaves is needed because of great potential inside it. One of standardization is testing the moisture content, water-soluble extract content, and ethanol-soluble extract content of kersen leaves simplicia. This research aims to determine the moisture content, water-soluble extract content, and ethanol-soluble extract content of kersen leaves simplicia. The method used in this research is the posttest only design. The kersen leaves are dried in an oven at 50°C for 24 hours and then be mashed using a grinder and sieved until they become powder. The testing of moisture content, water-soluble extract content, and ethanol-soluble extract content was conducted using the gravimetric method. The test results were analyzed descriptively and compared with previous literature. The result of average moisture content on kersen leaves was 6.15±0.03%; the water-soluble extract and ethanol-soluble extract of kersen leaves were 4.05±0.09% and 5.75±0.05%. Based on the results showed that the moisture content of kersen leaves has complied with the requirements of <10%. Meanwhile, the ethanol-soluble extract content of kersen leaves has higher than the water-soluble extract content, this concluded that a content of kersen leaves has non-polar characteristic.